SELF-DISCLOSURE TECHNIQUES TO INCREASE SELF-CONFIDENCE IN WOMEN WITH HIV/AIDS : CASE STUDY ON "M" IN THE INDONESIAN FAMILY PLANNING ASSOCIATION, SOUTH E RA SUMATRA - Nissa, Khairun; Razzaq, Abdur; Putra, Bela Janare (Jurnal Konseling Pendidikan Islam, 2024)
This research is entitled Individual Counseling Using Self-Disclosure Techniques to Increase Self-Confidence in Women Suffering from HIV/AIDS (Case Study on "M" at the Indonesian Family Planning Association, South Sumatra). The background to this research is based on problems that occur with clients where clients experience a sense of lack of self-confidence as a person with B20. This research aims to determine individual counseling using Self Disclosure techniques to increase self-confidence. The method used in this research is a qualitative approach using field research. The data collection techniques use observation, interviews and documentation methods. Meanwhile, the data analysis techniques used are pattern matching, data explanation and time series analysis. The results of this research show that there are two factors that influence client M's self-confidence, namely internal and external factors. After using the Self Disclosure technique, there appeared to be a change where client M had experienced changes in increasing his self-confidence.